A minor groove binder probe real-time PCR assay for discrimination between type 2-based vaccines and field strains of canine parvovirus - Decaro, Nicola (J Virol Methods, 2006)
A minor groove binder (MGB) probe assay was developed to discriminate between type 2-based vaccines and field strains of canine parvovirus (CPV). Considering that most of the CPV vaccines contain the old type 2, no longer circulating in canine population, two MGB probes specific for CPV-2 and the antigenic variants (types 2a, 2b and 2c), respectively, were labeled with different fluorophores. The MGB probe assay was able to discriminate correctly between the old type and the variants, with a detection limit of 10(1) DNA copies and a good reproducibility. Quantitation of the viral DNA loads was accurate, as demonstrated by comparing the CPV DNA titres to those calculated by means of the TaqMan assay recognising all CPV types. This assay will ensure resolution of most diagnostic problems in dogs showing CPV disease shortly after CPV vaccination, although it does not discriminate between field strains and type 2b-based vaccines, recently licensed to market in some countries.